The “SUPER” Program to Increase Marital Satisfaction - Ika Rizki Ramadhani; Tina Afiatin (Faculty of Psychology, Universitas Gadjah Mada, 2020)
A successful marriage can be achieved by aiming for a satisfying marriage. The low level of marital satisfaction causes various problems in marriage that might lead to divorce. The aim of this study was to determine the effect of the “SUPER” program in increasing marital satisfaction. The